Lactucin, a Bitter Sesquiterpene from Cichorium intybus, Inhibits Cancer Cell Proliferation by Downregulating the MAPK and Central Carbon Metabolism Pathway - Khandaker Md Sharif Uddin Imam; Yu Tian; Fengjiao Xin; Yingying Xie; Boting Wen (Molecules, 2022)
Lung cancer, especially adenocarcinoma, is the second most occurring and highest fatality-causing cancer worldwide. Many natural anticancer compounds, such as sesquiterpene lactones (SLs), show promising anticancer properties. Herein, we examined Lactucin, an SL from the plant Cichorium intybus, for its cytotoxicity, apoptotic-inducing, cell cycle inhibiting capacity, and associated protein expression. We also constructed a biotinylated Lactucin probe to isolate interacting proteins and identified them. We found that Lactucin stops the proliferation of A549 and H2347 lung adenocarcinoma cell lines while not affecting normal lung cell MRC5. It also significantly inhibits the cell cycle at G0/G1 stage and induces apoptosis. The western blot analysis shows that Lactucin downregulates the MAPK pathway, cyclin, and cyclin-dependent kinases, inhibiting DNA repair while upregulating p53, p21, Bax, PTEN, and downregulation of Bcl-2. An increased p53 in response to DNA damage upregulates p21, Bax, and PTEN. In an activity-based protein profiling (ABPP) analysis of A549 cell’s protein lysate using a biotinylated Lactucin probe, we found that Lactucin binds PGM, PKM, and LDHA PDH, four critical enzymes in central carbon metabolism in cancer cells, limiting cancer cells in its growth; thus, Lactucin inhibits cancer cell proliferation by downregulating the MAPK and the Central Carbon Metabolism pathway.